Intravenous lignocaine pretreatment to prevent intraocular pressure rise following suxamethonium and tracheal intubation. Issue 8 (August 1986) - Murphy, D F; Eustace, P; Unwin, A; Magner, J B
Abstract : Intravenous lignocaine (1.5 mg kg-1) was evaluated in patients undergoing intraocular surgery as a means of preventing the rise in intraocular pressure which accompanies tracheal intubation. In patients given either suxamethonium or pancuronium to facilitate tracheal intubation, lignocaine pretreatment conferred no benefit over placebo in preventing the intraocular hypertensive response.